PERAN MAHASISWA DALAM MENINGKATKAN PENDIDIKAN KARAKTER ANAK USIA DINI DI DESA PERKEBUNAN TOLAN I/II KAMPUNG RAKYAT - Muhammadong; Zainal Efendi Hasibuan; Gede Bagus Wira Diputra (Yayasan Baitul Hikmah al-Zain, 2024)
This service aims to improve character education for early childhood in families in Tolan I/II plantation villages. The problem raised in this research is the role of students in Tolan I/II Plantation villages as educators for children. The results of the research show that the character values ​​given by students to children in Tolan I/II Hamlet II plantation villages include: students train self-discipline in children, train perseverance, responsibility from an early age, humble attitude towards others, Cultivate good manners, uphold the values ​​of honesty, love for Allah by getting used to worshiping on time.